Алгебраїчні атаки на потокові шифратори як узагальнення кореляційних атак - Pometun, S. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
New Boolean’s function concepts, such as correlation with a known function value and Boolean’s function extension, are introduced. Algebraic attacks on stream ciphers with linear feedback are shown to be reduced to approximation of the nonlinear filter using low-degree polynomials in terms of the correlation with the known function value. This kind of correlation can also be used in describing algebraic attacks on other types of ciphers.